LOCAL WISDOM OF TABOOS IN KARO LANGUAGE - Jumat Barus; Robert Sibarani; Amrin Saragih; Mulyadi Mulyadi (Universitas Islam Sumatera Utara (UISU), 2018)
This research aims to explore local wisdom of taboos in Karo language. Taboo is more than prohibitions and avoidance in tradition; it normally arises from social restrictions on individual behaviour that can lead to inconvenience and danger. Taboo was created as a control for community to avoid personal and family conflict. The research was conducted in five sub-districts of Karo, North Sumatra Province, Indonesia. It was carried out by using a qualitative approach with ethnographic methods. The data of local wisdom were obtained from the interview method from nine key informants who mastered and used Karo language and culture well in their daily activities and the writer played a role as the native speaker so that he could directly feel how the culture was implemented in the daily lives of Karo society. It was found that the local wisdoms of taboos in Karo culture were attitude and eagerness to do the best for the community, since taboo rules provide a picture for them about how to express dignified words and behave glorious deeds and how to avoid mentioning disgusting words and behaving impolite manners. The rules become controls for social harmony to be maintained properly. Taboo rules were imposed not to make the society difficult to communicate with each other, but to provide a sense of security and peace for them so that they can live peacefully and harmoniously.